3D printing antagonistic systems of artificial muscle using projection stereolithography. (9th September 2015) - Peele, Bryan N; Wallin, Thomas J; Zhao, Huichan; Shepherd, Robert F
Abstract: The detailed mechanical design of a digital mask projection stereolithgraphy system is described for the 3D printing of soft actuators. A commercially available, photopolymerizable elastomeric material is identified and characterized in its liquid and solid form using rheological and tensile testing. Its capabilities for use in directly printing high degree of freedom (DOF), soft actuators is assessed. An outcome is the ∼40% strain to failure of the printed elastomer structures. Using the resulting material properties, numerical simulations of pleated actuator architectures are analyzed to reduce stress concentration and increase actuation amplitudes. Antagonistic pairs of pleated actuators are then fabricated and tested for four-DOF, tentacle-like motion. These antagonistic pairs are shown to sweep through their full range of motion (∼180°) with a period of less than 70 ms.